PENGARUH PENERAPAN SISTEM MANAJEMEN SUMBER DAYA PERUSAHAAN (ERP) DALAM MENINGKATKAN KINERJA MANAJEMEN RANTAI PASOK (SCM) PT NESTLE INDONESIA - Elzagi, Verliana; Febiana, Anjela Rini; Eviyani, Estin Rose; Yeronica, Fernanda; Melissa; Risvi, Hellena; Yuwono, Wisnu; Sinambela, Fitriana Aidnilla (MANABIS: Jurnal Manajemen dan Bisnis, 2023)
The development of information technology has enabled companies to simplify their business processes, face challenges and meet customer demands. ERP is one of the information technologies commonly used by companies. In order for a business to compete with its competitors, strong performance is needed which is supported by supply chain management by operating as efficiently as possible with the help of information technology. The Nestlé company is an important component of the corporation and global food supply as the world's largest food producer. Nestlé companies implement various types of information technology tools in SCM, such as ERP systems to help manage their supply chain. Nestle has developed an ERP system based on SAP, which helps improve its business processes and achieve competitive advantage in the industry and significantly improves Nestle's supply chain management performance by increasing efficiency, reducing operational costs and improving product quality